Novel approach to meniscal vascularity evaluation using indocyanine green fluorescence-guided knee arthroscopy - Tamiko Kamimura (BMJ Surgery, Interventions, & Health Technologies)
Objectives This study aimed to use indocyanine green (ICG) fluorescence-guided knee arthroscopy to observe the meniscus and surrounding tissue vascularity and determine correlation with the patients’ backgrounds. Currently, no data are available on the clinical application of ICG fluorescence-guided knee arthroscopy in assessing meniscal vascularity.Design Prospective, case series.Setting In-hospital settings.Participants 41 knees of 34 patients were examined. 4 knees of 4 patients were included in a pilot study for technique refinement only, while the remaining 37 knees of 30 patients were included in the study.Main outcome measures The times from ICG administration to fluorescence onset and fluorescence duration from onset to complete attenuation were recorded. The fluorescence intensity at the anterior, middle, and posterior segments of the meniscus was evaluated on a 4-point scale. The younger and older and smoker and non-smoker groups were compared.Results The average fluorescence onset time was 32.05 s, whereas the average fluorescence duration was 11 min 14 s. The age groups aged≤45 and ≥46 years showed an onset of 30±24.9 and 33.17±16.2 s and a duration of 12 min 54 s and 10 min 20 s, respectively. The smoking and non-smoking groups exhibited an onset of 28.33±14.4 and 33.84±21.5 s and a duration of 10 min 37 s and 11 min 32 s, respectively. All segments of the lateral meniscus showed higher fluorescence intensities than the medial. The posterior segment of the lateral meniscus at ≤45 was markedly more fluorescent and significantly different from ≥46.Conclusions Fluorescence was observed for approximately 30 s after intravenous ICG injection and lasted approximately 10 min. Fluorescence intensity was brighter in the posterior segment of the lateral meniscus, particularly at ≤45. ICG fluorescence-guided knee arthroscopy may assist in case-specific hemodynamics and real-time surgical evaluation of the meniscus in living humans.